Supravalvular aortic stenosis in a twin. Issue 10 (October 1978) - Neilson, G; Hossack, K F
Abstract : A case of subvalvular aortic stenosis in one of a set of dissimilar twins is reported. The case is discussed in terms of the aetiological factors involved and supports the view that supravalvular aortic stenosis is not environmental and may be genetic in origin.